Antimicrobial Resistance Genes in Legionella from Artificial Water Systems - Pereira, Bernardo Beirão (2024)
Background: Legionella species are the causative agent of Legionnaires’ disease and, as ubiquitous waterborne bacteria, are prone to antimicrobial resistance gene (ARG) acquisition and dissemination due to the antimicrobial contamination of natural environments. Given the potential health risks associated with ARGs, it is crucial to assess their presence in the Legionella population. Methods: The ARGs lpeAB and tet56 were detected in 348 samples, isolates, and DNA extracts using conventional PCR. In a subset of lpeAB-positive isolates, azithromycin (AZT) MIC values were obtained using the EUCAST protocol and LpeAB activity was evaluated through an efflux pump inhibition assay. Results: The lpeAB gene was found in 19% (66/348) of samples, with higher detection rates in the L. pneumophila and L. pneumophila sg1 subgroups, at 30% and 41%, respectively. A positive association between lpeAB and L. pneumophila sg1 was found. The MIC values of the lpeAB-positive isolates ranged from 0.064 to 2 mg/L. LpeAB inhibition resulted in 2- and 4-fold MIC reductions in 10 of the 13 isolates analyzed. One sample each of L. longbeacheae and L. bozemanae was found to possess the tet56 gene. Conclusions: The lpeAB gene is predominant in L. pneumophila sg1. A few isolates with the lpeAB gene exhibited MIC values below the EUCAST tentative highest MIC values for wild-type isolates. Expanding ARG monitoring in Legionella is essential to assess the public health risk of Legionnaires’ disease.